بناء دليل مقترح للتربية العملية بكليات التربية الرياضية في ضوء معايير الجودة الشاملة - النبراوي، إيهاب سعد عبدالعزيز (جامعة المنصورة - كلية التربية الرياضية, 2016)
This study aimed to build a proposed process for breeding guide, in light of the overall quality standards and to achieve the objectives of the study, the researcher drafted (56) standard TQM in the field of practical education has been judged by a group of experts in the field of quality, where he was writing guide phrases in the light within four It is the proposed manual axes (the goals of practical education, content of education process, the tasks involved in education process, elements of the student teacher calendar) in the form of a questionnaire to measure the importance of each phrase and after confirmation of the validity and reliability have been intentional sample included faculty concerned members of overall quality in some colleges of education target Sports to answer paragraphs, where the results of the study components of the index showed in the overall quality light as follows: First: the objectives of the process of education: (14) goals have been accepted by all of the study sample. Second: The content of practical education: (21) is accepted by all of the study sample. Third: The functions of each member of the parties concerned with education process: Supervisor Academic (12) mission has been accepted all, the teacher collaborator (13) mission has been accepted, the school principal (12) mission has been accepted the student teacher (15) mission has been accepted (13) of them It was important refused to lower their importance and according to the opinion of the study population. Fourth: The calendar items Tallb teacher (22) element has been accepted by all of the study.
هدفت هذه الدراسة لبناء دليل مقترح للتربية العملية، في ضوء معايير الجودة الشاملة، ولتحقيق أهداف الدراسة قام الباحث بصياغة (56) معيارا للجودة الشاملة في مجال التربية العملية تم تحكيمها من مجموعة من الخبراء في مجال الجودة، حيث تم كتابة عبارات الدليل في ضوئها ضمن أربع هي محاور الدليل المقترح (أهداف التربية العملية، محتوى التربية العملية، مهام المعنيين بالتربية العملية، عناصر تقويم الطالب المعلم) على شكل استبانة لقياس أهمية كل عبارة وبعد التأكد من صدقها وثباتها تم استهداف عينة قصدية شملت أعضاء هيئة التدريس المعنيين بالجودة الشاملة في بعض كليات التربية الرياضية للإجابة على فقراتها، حيث أظهرت نتائج الدراسة مكونات الدليل في ضوء الجودة الشاملة كما يلي: أولا: أهداف التربية العملية: (14) هدفا تم قبولها جميعا من قبل عينة الدراسة. ثانيا: محتوى التربية العملية: (21) عبارة تم قبولها جميعا من قبل عينة الدراسة. ثالثا: مهام كل فرد من المعنيين بالتربية العملية: المشرف الأكاديمي (12) مهمة تم قبولها جميعا، والمعلم المتعاون (13) مهمة تم قبولها، مدير المدرسة (12) مهمة تم قبولها، الطالب المعلم (15) مهمة تم قبول (13) منها وتم رفض مهمتين لانخفاض أهميتها وفقا لرأى مجتمع الدراسة رابعا: عناصر تقويم الطالب المعلم (22) عنصرا تم قبولها جميعا من قبل الدراسة.
26804
Keywords: التربية العملية -- الطالب المعلم -- معايير الجودة الشاملة -- كليات التربية الرياضية